Decision modelling for the evaluation of diabetes outcomes - A. A. Mosikian; W. Zhao; T. L. Galankin; A. S. Kolbin (Фармакоэкономика, 2017)
The process of decision modelling in diabetes mellitus (DM) is often complicated by comorbidity among diabetic patients, complexity of endpoint selection, and unclear time horizons. Aim. To review the available recommendations, relevant methods and mathematical approaches to decision modelling in DM. Materials and Methods. We searched through the PubMed database using the ResearchGate and Mendeley networks; we also collected data from the websites of the key opinion leaders in the field of pharmacoeconomics and decision modelling. Results. This review contains up-to-date information on the validity of the most common DM decision models and on the validity of extrapolating the type 2 DM models to patients with type 1 DM. We also provide some clinically relevant comments on the American Diabetes Association’s requirements concerning the decision models in DM. The review incorporates data on the current mathematical approaches to modelling the changes in glycated hemoglobin levels, the body mass index and the quality-adjusted life expectancy – for both type 1 and type 2 DM. Conclusion. Despite recent successes in DM decision modelling, the existing approaches are not always relevant to some groups of DM patients or to some aspects of the disease. Thus, the use of the novel anti-diabetic drugs (liraglutide, semaglutide, empagliflozin) capable of significantly reducing cardiovascular risks in DM patients, require new approaches to decision modelling in diabetes mellitus.